Effect of electrical activity of the diaphragm waveform patterns on SpO2 for extremely preterm infants ventilated with neurally adjusted ventilatory assist - Araki, Ryosuke; Tomotaki, Seiichi; Akita, Mitsuyo; Motokura, Kouji; Tomobe, Yutaro; Yamauchi, Takeru; Hanaoka, Shintaro; Tomotaki, Hiroko; Iwanaga, Kogoro; Niwa, Fusako; Takita, Junko; Kawai, Masahiko (Pediatric pulmonology, 2021)
Objective This study aimed to evaluate the association between electrical activity of the diaphragm (Edi) waveform patterns and peripheral oxygen saturation (SpO2) in extremely preterm infants who are ventilated with neurally adjusted ventilatory assist (NAVA). Study Design We conducted a retrospective cohort study at a level III neonatal intensive care unit. Extremely preterm infants born at our hospital between November 2019 and November 2020 and ventilated with NAVA were included. We collected Edi waveform data and classified them into four Edi waveform patterns, including the phasic pattern, central apnea pattern, irregular low‐voltage pattern, and tonic burst pattern. We analyzed the Edi waveform pattern for the first 15 h of collectable data in each patient. To investigate the association between Edi waveform patterns and SpO2, we analyzed the dataset every 5 min as one data unit. We compared the proportion of each waveform pattern between the desaturation (Desat [+]) and non‐desaturation (Desat [–]) groups. Results We analyzed collected data for 105 h (1260 data units). The proportion of the phasic pattern in the Desat (+) group was significantly lower than that in the Desat (–) group (p < .001). However, the proportions of the central apnea, irregular low‐voltage, and tonic burst patterns in the Desat (+) group were significantly higher than those in the Desat (–) group (all p < .05). Conclusion Our results indicate that proportions of Edi waveform patterns have an effect on desaturation of SpO2 in extremely preterm infants who are ventilated with NAVA.